PSYCHOLOGICAL ANALYSIS OF HARLEY QUINNâ€™S PERSONALITY IN â€œBIRDS OF PREYâ€ MOVIE - Wirawan, I Putu Andy (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTThis study analyzies the psychological analysis of Harley Quinn as the main character in â€œBirdsof Preyâ€ movie. Theory of Human Motivation proposed by Maslow (1970) was used to analyzeHarleyâ€™s personality through the fulfillment of five-level needs that can show her personality;namely physiology, safety, love and belongingness, esteem, and self-actualization needs.â€œBirds of Preyâ€ movie with the scope of limitation of Harleyâ€™s speeches, actions, and dialoguesare chosen as the source of data. The data were collected qualitatively and analyzed applyingthe theory of Human Motivation. The findings were presented descriptively with descriptionsin sentences and paragraphs. As the result, Harley shows herself as a kind, dramatic, vicious,realistic, optimistic, trustworthy, and independent woman. The way how Harley fulfilled allneeds and the motivation behind each of them are the overviews of her personality. A desire oflooking for emancipation causes Harley to fulfill the five needs that indirectly show herpersonality.Keywords: psychology, Harley Quinn, personality, human motivation theoryABSTRAKKajian ini membahas tentang analisis psikologis Harley Quinn sebagai pemeran utama dalamfilm â€œBirds of Preyâ€. Teori Human Motivation yang dikemukakan oleh Maslow (1970)digunakan untuk menganalisis kepribadian Harley melalui pemenuhan lima tingkat kebutuhanyang dapat menunjukkan kepribadiannya; yaitu kebutuhan fisiologi, keamanan, cinta dankepemilikan, harga diri, dan aktualisasi diri. Film â€œBirds of Preyâ€ dengan cakupan batasancara bicara, aksi, dan dialog Harley dipilih sebagai sumber data. Data dikumpulkan secarakualitatif dan dianalisis dengan menggunakan teori Human Motivation. Hasil penelitiandisajikan secara deskriptif dengan uraian dalam kalimat dan paragraf. Sebagai hasilnya,Harley menunjukkan dirinya sebagai wanita yang baik hati, dramatis, kejam, realistis, optimis,dapat dipercaya, dan mandiri. Cara Harley memenuhi semua kebutuhan dan motivasi dibaliknya adalah gambaran umum tentang kepribadiannya. Keinginan mencari emansipasimenyebabkan Harley memenuhi lima kebutuhan yang secara tidak langsung menunjukkankepribadiannya.Kata kunci: psikologi, Harley Quinn, kepribadian, teori human motivation